PENGARUH RASIO KEUANGAN TERHADAP KEBIJAKAN DIVIDEN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL INTERVENING - Lestari, Idah Ayu; Priyadi, Maswar Patuh (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThe purpose of this research is to prove the influence profitability (ROA), leverage (DER), liquidity (CR), and growth (TAG) to the dividend policy (DPR) by considering good corporate governance (CGPI ) as the intervening variable. The population is all companies which are ranked by the Indonesian Institute for Corporate Governance (IICG) in 2010-2014 periods. The samples are 8 companies which have been selected by using purposive sampling method. The data analysis has been done by using multiple linear regressions to identify the independent variables which give influence to the dependent variable and path analysis is to detect the indirect influence through good corporate governance. The result of the F test shows that all independent variables give significant influence to the dividend policy through the implementation of good corporate governance. The result of t-test shows that profitability, liquidity, growth, and good corporate governance do not give significant influence to the dividend policy whereas the leverage gives significant influence to the dividend policy. It has been found from the result of the path analysis that the implementation of good corporate governance is not proven to give influence as the intervening variable.Keywords: Profitability, leverage, liquidity, growth, good corporate governance, dividend payout ratio.